Acuphagia on the Obsessive-Compulsive Spectrum in an Adolescent Male. (29th October 2020) - Butler, William; Allen, Luis
Abstract : Background . Pica is a condition that is commonly missed in childhood. This condition occurs worldwide and is considered normal in children from ages 18- to- 36 months. It is also commonly seen in pregnant women due to associated nutritional deficiencies. Acuphagia is a subtype of pica which has been briefly described in the literature. Its classification has been speculated to belong on a spectrum of obsessive-compulsive disorders (OCD). This case involves Mr. C, a 16-year-old male with a history of depression, anxiety, and ten previous intentional foreign body ingestions involving sharp objects such as needles, forks, and thumbtacks. He states that he recently ate a nail and denies any current obsessions. He was admitted from a local involuntary receiving facility due to decreased bowel movements in the last week. Learning points and recommendations for practitioners are described.